Removal of dimethylphenols and ammonium in laboratory‐scale horizontal subsurface flow constructed wetlands. Issue 12 (2nd November 2017) - Schultze‐Nobre, Luciana; Wiessner, Arndt; Bartsch, Cindy; Paschke, Heidrun; Stefanakis, Alexandros I.; Aylward, Lara A.; Kuschk, Peter
Abstract: Phenolic compounds in industrial wastewaters are toxic pollutants and pose a threat to public health and ecosystems. More recently, focus is being directed toward combining the treatment of these compounds with a cost‐effective and environmentally sound technology. The removal efficiency of dimethylphenol and ammonium nitrogen was studied, for the first time, in three different laboratory‐scale horizontal subsurface flow constructed wetlands planted with Juncus effusus . Two of the wetlands used were filled with gravel. One of these was planted and the second left without vegetation. The third wetland was a hydroponic system. It was found that the removal efficiencies of dimethylphenol was dependent on the inflow loading of the contaminant and was higher in the planted systems. Both planted systems yielded 99% removal efficiency up to loads of 240 mg/d, compared to only 73% for the unplanted constructed wetland. Factors and processes such as redox dynamics, methanogenesis, reduction of ammonium and low nitrate and nitrite concentrations imply simultaneous aerobic and anaerobic dimethylphenol transformations. A significant surplus of organic carbon was detected in the planted wetlands, which may originate from intermediates of the dimethylphenol transformation processes and/or organic plant root exudates. The present study demonstrates that horizontal subsurface flow constructed wetlands are a promising alternative system for the treatment of effluents contaminated with dimethylphenol isomers.